2015
DOI: 10.1177/1049732314566328
|View full text |Cite
|
Sign up to set email alerts
|

“Getting the Left Right”

Abstract: We used a phenomenological approach to gain insight into the experiences of self, other, and world in patients with hemispatial neglect within the first month following stroke. Comprehensive descriptions of circumstances were conjoined with open-ended interviews of 12 participants. The neglect experience was captured in the overarching theme, "getting the left right," which encompasses the two subthemes of (a) surreal awareness of the left and (b) emergence of a different world. Patients had unclear perception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…4 For a concrete example of how such concepts can ground observational research, we will turn to one of the authors' empirical studies of neglect. Participants included 12 neglect hospital admitted patients (8 women) with moderate to severe neglect within 21 days following stroke (Klinke et al, 2015). Finding the most fruitful concepts to ground the data collection and analysis was a time-consuming and laborious endeavor.…”
Section: An Example Of Conceptual Grounding In An Observational Study Of Neglectmentioning
confidence: 99%
See 2 more Smart Citations
“…4 For a concrete example of how such concepts can ground observational research, we will turn to one of the authors' empirical studies of neglect. Participants included 12 neglect hospital admitted patients (8 women) with moderate to severe neglect within 21 days following stroke (Klinke et al, 2015). Finding the most fruitful concepts to ground the data collection and analysis was a time-consuming and laborious endeavor.…”
Section: An Example Of Conceptual Grounding In An Observational Study Of Neglectmentioning
confidence: 99%
“…Any additional pursuing was not possible because she became upset when her performance was questioned. (Klinke et al, 2015(Klinke et al, , 1629 Pursuing specific events of misperceived affordances in the remaining 11 study participants revealed that memories of events occurring on their left side, including verbal information provided within the neglected space, often faded over time or were replaced by confabulations. In a similar manner, other distinctive features of neglect emerged throughout the study when the researcher interrogated misperceived affordances.…”
Section: An Example Of Conceptual Grounding In An Observational Study Of Neglectmentioning
confidence: 99%
See 1 more Smart Citation
“…The two authors subsequently conducted separate quality assessments on 35 studies. Eventually, 34 studies met the quality criteria,38–71 and 1 study was excluded 72. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020 flow diagram (figure 1) presents the process for selecting and identifying the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen studies (52.9%) conducted single interviews at one time point only,41 43 47 49 51–53 58 61–67 69–71 14 studies (41.2.%) conducted repeated interviews38–40 42 44–46 48 50 54–57 68 and 2 studies (5.9%) conducted both repeated and one-off interviews 59 60. Regarding the data analysis approach, 19 studies (55.9%) adopted a phenomenological or hermeneutic approach,38–40 42 43 45 47 48 51 53–58 63 65 67 68 3 studies (8.8%) adopted a narrative approach,46 50 61 3 studies (8.8%) adopted an interpretative inductive or descriptive approach,64 69 70 2 studies (5.9%) adopted a grounded theory approach,66 71 2 studies (5.9%) adopted an ethnographic approach,44 60 1 study (2.9%) adopted a deductive content analysis approach,52 1 study (2.9%) adopted a phenomenographical approach,41 1 study (2.9%) adopted both phenomenological and ethnographic approaches,62 and 2 studies (5.9%) did not clearly state their methodological orientation 49 59. Three overarching analytical themes were identified, namely, ‘disconnection between oneself, others and the world,’ ‘the transitional period: exploring and negotiating’, and ‘reconnecting with oneself, others and the world’.…”
Section: Resultsmentioning
confidence: 99%